Microbiological Quality Assessment of Water and Fish from Karst Rivers of the Southeast Black Sea Basin (Croatia), and Antimicrobial Susceptibility of Aeromonas Isolates - Kolda, Anamarija; Mujakić, Izabela; Perić, Lorena; Vardić Smrzlić, Irena; Kapetanović, Damir (Current microbiology, 2020)
Karst rivers are of great interest for commercial fishing and aquaculture, yet they are quite vulnerable aquatic environments because the permeable karst rocks do not effectively filter out contaminants. To understand the current state of karst rivers water quality, we analysed the physico-chemical and microbiological parameters, focusing on antibiotic pollution and the emergence of antibiotic-resistant microbes of three such rivers in Croatia. Water quality varied between classes I and II across sampling sites, and the numbers of total coliforms, enterococci and heterotrophic bacteria varied substantially among sites. Swabs from fish gills, spleen, liver and kidneys were cultured and 94 isolates identified by MALDI-TOF mass spectrometry. The predominant genus was Aeromonas (42.5% of all identified isolates), known for its adaptability to polluted environments and its frequent association with antibiotic resistance. Of the selected Aeromonas isolates known as most pathogenic, half were resistant to at least three antibiotic categories. The Enterobacteriaceae family was represented by the greatest number of genera, most of which are pathogenic for humans and animals and are spoilage bacteria for fish. The results of this study highlight the extent of antibiotic contamination in aquatic environments and the increasing threat of pathogenic and spoilage bacteria in traditionally high-quality karst rivers.
Keywords: Microbial Sensitivity Tests; Rivers; řeky; mikrobiální testy citlivosti; Animals; Water; Humans; Aeromonas; Anti-Bacterial Agents; lidé; Black Sea; antibakteriální látky; Černé moře; Croatia; Chorvatsko; voda; zvířata